Understanding online purchasing behaviour after COVID-19: an extended technology acceptance model with motivations learnt from the pandemic - Karina Adomaviciute-Sakalauske; Sigitas Urbonavicius (Cogent Business & Management, 2024)
Although the COVID-19 pandemic has been overcome, the balance between offline and online buying has not returned to pre-pandemic ratios. Statistics even show that online shopping continues to grow. This study develops a theoretical model that explains the growing use of online purchasing by integrating the lingering effects of motivational factors learnt during the COVID-19 pandemic into the technology acceptance model. Three types of motivational factors (perceived risks, acquired skills, and experienced benefits) are defined based on a performed literature analysis. Using a rather unique approach their motivational impact during the pandemic and lingering effects after it conventionalised within the framework of the technology acceptance model, thus extending the latter with factors identified during the COVID-19 pandemic and offering new research avenues for researching online buying behaviours.
Keywords: 650; COVID-19; technology acceptance model; learnt motivations; online buying; perceived risks; acquired skills; experienced benefits